Can N, S Cocoordination Promote Single Atom Catalyst Performance in CO2RR? Fe‐N2S2 Porphyrin versus Fe‐N4 Porphyrin. Issue 29 (18th June 2021) - Cao, Shoufu; Wei, Shuxian; Wei, Xiaofei; Zhou, Sainan; Chen, Hongyu; Hu, Yuying; Wang, Zhaojie; Liu, Siyuan; Guo, Wenyue; Lu, Xiaoqing
Abstract: Single atom catalysts (SACs) are promising electrocatalysts for CO2 reduction reaction (CO2 RR), in which the coordination environment plays a crucial role in intrinsic catalytic activity. Taking the regular Fe porphyrin (Fe‐N4 porphyrin) as a probe, the study reveals that the introduction of opposable S atoms into N coordination (Fe‐N2 S2 porphyrin) allows for an appropriate electronic structural optimization on active sites. Owing to the additional orbitals around the Fermi level and the abundant Fe d z 2 orbital occupation after S substitution, N, S cocoordination can effectively tune SACs and thus facilitating protonation of intermediates during CO2 RR. CO2 RR mechanisms lead to possible C1 products via two‐, six‐, and eight‐electron pathways are systematically elucidated on Fe‐N4 porphyrin and Fe‐N2 S2 porphyrin. Fe‐N4 porphyrin yields the most favorable product of HCOOH with a limiting potential of −0.70 V. Fe‐N2 S2 porphyrin exhibits low limiting potentials of −0.38 and −0.40 V for HCOOH and CH3 OH, respectively, surpassing those of most Cu‐based catalysts and SACs. Hence, the N, S cocoordination might provide better catalytic environment than regular N coordination for SACs in CO2 RR. This work demonstrates Fe‐N2 S2 porphyrin as a high‐performance CO2 RR catalyst, and highlights N, S cocoordination regulation as an effective approach to fine tune high atomically dispersed electrocatalysts. Abstract : Fe‐N2 S2 porphyrin exhibits higher CO2 reduction reaction activity toward HCOOH and CH3 OH products than Fe‐N4 porphyrin. N, S cocoordination can effectively tune electronic structures of single atom catalysts and thus provide better catalytic environment for intermediates binding than regular N coordination. N, S cocoordination regulation might be an effective approach to fine tune high atomically dispersed electrocatalysts.